Synthesis, In Vitro Antitumor Activity and Molecular Mechanism of Novel Furan Derivatives and their Precursors - Lu, Dan; Zhou, Ya; Li, Qin; Luo, Juan; Jiang, Qihua; He, Baicheng; Tang, Qiang (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Compounds featuring furan nucleus exhibit diverse biological properties. Lots of furan derivatives have been explored as pharmaceutical compounds. Hence it is of great interest to explore furan derivatives and their precursors as antitumor agents. Objective: A series of novel furan derivatives and their precursors (1-36) were synthesized from α-haloketones and β-dicarbonyl compounds. Methods: The reactions between β-dicarbonyl compounds and α-haloketones under basic conditions produced tricarbonyls or dihydrofurans, which were then condensed into their corresponding furan products. Their potential antiproliferative activity in vitro against two human tumor cell lines-cervical (HeLa) and colorectal (SW620) was evaluated using CCK-8 assay. Compounds 1 and 24 were selected for Western blot analysis. Results: Pronounced anti-proliferative effect in the micromolar level was observed for compounds (1, 4, 17, 20, 21, 24, 27, 31 and 32) in HeLa cells, with their IC50 values ranging from 0.08 to 8.79μM. Additionally, furan compounds (24, 26, 32 and 35) had moderate to potent anti-proliferative activity against the SW620 cell line. Furthermore, the possible targets of these compounds were explored by Western blot analysis. The results indicated that the candidates (compounds 1 and 24) exhibited excellent antiproliferative activity, which may be mediated by promoting the activity of PTEN to suppress PI3K/Akt and Wnt/β-catenin signaling. Conclusion: Most of the furan derivatives and their precursors reported herein exhibited moderate to excellent anti-proliferative activity against HeLa cell line and/or SW620 cell line. Compounds 1 and 24, as well as their analogues may be developed as promising anti-cancer agents.
Keywords: PI3K/Akt